Formulasi Bacillus sp. Sebagai Bionematisida Terhadap Meloidogyne incognita - Erna Indah Dwi Safitri (Fakultas Pertanian, 2025)
Meloidogyne incognita is a parasitic nematode that is detrimental to horticultural crops, especially tomatoes. The use of chemical pesticides to control nematodes can pollute the environment, so sustainable, environmentally friendly alternatives are needed. One of them is by using Bacillus sp. bacteria as a biological agent. This study aims to determine the effect of various carrier media on the quality of Bacillussp. formulations, cell viability during storage, and their effectiveness in controlling M. incognita in vitro. The method used was a Completely Randomized Design (CRD) with 5 treatments and 5 replications. The results showed that all bionematicide formulations with a water content of <20% were able to maintain the population of Bacillus sp. in the formulation for 70 days of storage. The bran and sawdust formulations were effective in inhibiting nematode egg hatching by 91.4%. Meanwhile, the vermicompost formulation could increase mortality (J2) by 24.8%. In conclusion, organic material formulations such as bran, sawdust, and compost are effective as Bacillus sp. based bionematicides. in biological control of M. incognita.
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: Meloidogyne incognita; Bacillus sp.; bionematicides; solid formulation; viability